Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s10620-014-3298-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Urgent Findings on Abdominopelvic CT in Patients with Crohn’s Disease Presenting to the Emergency Department

Abstract: Only 39 % of the APCTs performed in the ED among patients with CD showed urgent findings. Stricturing or penetrating disease, tachycardia, leukocytosis, and high CRP level were predictors of urgent CT findings, while biologic agent use was a negative predictor. To reduce unnecessary radiation exposure, the selection process for CD patients referred for APCT must be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…The ED evaluation of symptomatic CD patients frequently necessitates an APCT to identify clinically relevant complications such as fistulas, strictures, obstruction, perforation, and intraabdominal abscesses [1,4]. APCT imaging is typically warranted given the high rates of detecting serious CD complications ranging from 29-47% and the identification of intraabdominal abscesses in 9-18% of these ED encounters [4,[10][11][12]. There is an overall trend towards increased CT usage with concern for lifetime radiation exposure in this patient population [4].…”
Section: Discussionmentioning
confidence: 99%
“…The ED evaluation of symptomatic CD patients frequently necessitates an APCT to identify clinically relevant complications such as fistulas, strictures, obstruction, perforation, and intraabdominal abscesses [1,4]. APCT imaging is typically warranted given the high rates of detecting serious CD complications ranging from 29-47% and the identification of intraabdominal abscesses in 9-18% of these ED encounters [4,[10][11][12]. There is an overall trend towards increased CT usage with concern for lifetime radiation exposure in this patient population [4].…”
Section: Discussionmentioning
confidence: 99%
“…26,38,39 Despite recent improvements in CT use overall, rates of CT use in the ED have continued to increase, 40 a trend that some data suggest may also be the case for abdominopelvic CT in inflammatory bowel disease. 34,[41][42][43] These increases are likely due to many factors, including expectations of referring physicians for imaging in the ED. For patients who might be suitable for symptomatic treatment and discharge, absence of worrisome findings on ED imaging can provide clinicians and patients with confidence in a safe and prudent disposition.…”
Section: Imaging and Associated Radiation Exposure Among Patients Witmentioning
confidence: 99%
“…However, Kerner et al 41 found that during an 8-year period, CT use in ED patients with Crohn's disease increased from 47% to 78% of encounters, with no change in admission rate (68% in 2001 versus 71% in 2009) and no change in yield of CT. And yet, data also suggest that the yield of CT in identifying obstruction, perforation, abscess, or other urgent noninflammatory-bowel-disease-related diagnoses is fairly high, ranging from 32.1% to 38.7% in ED-based studies. 41,42,44,45 In a Canadian study of 152 patients with Crohn's disease and 130 with ulcerative colitis presenting to an ED over a 2-year period, CT was performed for 49% of the Crohn's disease patients and 19% of the ulcerative colitis patients and was believed to change clinical management in 80% and 69% of encounters, respectively. 34 This was based on incompletely specified criteria but included disease requiring drainage, surgery, or other intervention.…”
Section: Imaging and Associated Radiation Exposure Among Patients Witmentioning
confidence: 99%
“…A proposed biochemical model using C‐reactive protein, erythrocyte sedimentation rate, and hematological parameters is purported to reduce CT imaging by 43% . Clear published guidelines for the acute assessment of Crohn's disease patients in the ED may be able to help identify those with “red flags” requiring urgent imaging and those that do not . Patients who have had a CT at admission do not need to have an MRE to complete assessment …”
mentioning
confidence: 99%